Evaluación de subproductos de Oryza sativa como sustratos naturales en la producción y viabilidad in vitro de conidias de Paecilomyces lilacinus - ROJAS FLORIAN, Ruth Marjorie (2019)
The objective of this work was to evaluate the byproducts of Oryza sativa in the production and percentage of in vitro viability of conidia of Paecilomyces lilacinus. For which they were used byproducts as bran and rice husk as substrates individually or in combination. The test systems were prepared and inoculated with a suspension of P. lilacinus of 106 conidia / mL and incubated at 25 ± 2 ° C for 10 days, then a count was carried out to determine the number of conidia per gram of substrate; Likewise, the viability percentage of each test system was determined by inoculating the previous suspension in potato dextrose broth and then counting in fresh with lactophenol blue. The production of conidia was observed in each evaluated test system, verifying that in the S5 (rice without husk and bran) the highest production of conidia was obtained in comparison with the control S1 (rice); whereas, in the systems S3 (bran) and S6 (husk and bran) a similar production was obtained, but lower than the previous ones, the lowest production of conidia was recorded in S2 (husk) followed by S4 (rice and husk); the viability percentages of the fungus were also observed in each of the test systems, obtaining the highest in S5 with 95%, followed by S1 with 93% and 91% in S3; the lowest percentages were obtained in S4, S6 and S2 with 89%, 81% and 21% respectively. The statistical analysis determined that there are significant differences, p <0.05, between the values of production and viability of conidia obtained in the test systems. It is concluded that the test system based on rice without husk and O. sativa bran allowed to obtain a higher yield in the production of conidia; whereas, this same assay system allowed obtaining a greater percentage of in vitro viability of the conidia of P. lilacinus in 10 days at 25 ± 2 ° C, but statistically there is no significant difference with the systems, based on rice without skin, and bran, evaluated individually.